QUALITY OF LIFE OF PATIENTS WITH DIMINISHED VISION - Tsvetomir Dimitrov; Tsvetelina Mihaylova; Desislava Todorova (Peytchinski Publishing, 2018)
The eye diseases cause sufferings, affect the quality of life of the patient, and decrease the level of his/her well-being. The disability, related to the diminution of vision, is an indicator for the medical condition of the population, state of morality and ethics in the society, and it may be corrective in the work of healthcare professionals. The aim of the study is an analysis of the significance and extent of the problem with reference to the quality of life of patients with poor vision. The task is an exploration of the quality of life in connection with eye disability, which to assist in selecting appropriate measures regarding the problem. The glaucoma is a serious, socially significant disease, which may lead to considerable loss of vision and to blindness if let untreated. A study of the primary disability during the period from the year 2005 to 2012, in Eastern Bulgaria, demonstrated that the glaucoma is a leading cause of bilateral blindness. The degree of vision reduction causes a considerable impact on the quality of life. The factor age influences negatively the quality of life in patients with loss of vision. The poorest quality of life (QoL) had the oldest, and the persons below 40 years of age. The assessment of the disability, and of the worsened QoL for patients with eye diseases and their families, as well as for the Bulgarian society, is of primary significance for the creation of positive practices as performing of screening programs, etc.